The Nonconformist movement in industrial Swansea, 1780-1914. - Edwin Colin Williams (1993)
This is a study of Nonconformity in industrial society of Swansea from about 1780 to 1914. Chapter I sets the scene by describing the economic and social background. From the late eighteenth century, industrial growth taking place nearby in the districts surrounding the ancient borough of Swansea transformed the character of the entire area, and resulted in the creation of a series of industrial communities during the course of the following century. The spotlight then turns upon Nonconformity. Earlier forms of the movement had existed in the district since the middle of the seventeenth century. Then, from the late eighteenth century, there was massive and sustained growth, which enabled it to become the dominant factor in the religious life of the locality by the middle of the following century. Subsequently, this position was consolidated and strengthened over the remainder of the century. The next chapters focus on certain aspects of the movement within the locality. Chapter III examines Nonconformity as a religion, its characteristics, preoccupations and the reasons for its popularity. Chapter IV then outlines those cultural and educational activities which were an integral part of Nonconformity and which contributed so much to its appeal and to its importance. Chapter V then considers Nonconformity and its relationship with the industrial society of the locality. Unlike the Established Church, the movement benefited from the emergence of the industrial society. This was because it was capable of providing the religious and other fundamental needs of a society experiencing traumatic change. However as the industrial society matured, these needs were diminished or were satisfied in other ways. The study concludes by stating that the industrial society in Swansea was associated with a vigorous and diverse Nonconformist movement. However, this society, which had initially contributed considerably to the growth of Nonconformity also added to the problems and challenges facing the movement as the nineteenth century drew to its close.